PENGARUH LOKASI TEMPAT TINGGAL DAN ADVERSITY QUOTIENT TERHADAP ADAPTASI PADA PERMUKIMAN - Deni Kurniawan (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2013)
ABSTRACT The research objectivewas to obtainempirical data on theeffect oflocation of residenceand adversity quotient to adaptation on settlements. The Ex Post Facto research using dependent variable: adaptation to settlement, independent variables: location of residence, while the independent variable attributes: low and high adversity quotient. The results showed the first hypothesis, third, and fourth that the location of residence has an influence on adaptation to settlement. This is evidenced bythereceipt ofsignificance, there are differences inadaptation tothe location ofsettlementsin bothsame results werealsoevidencedin thedifferent testgroupsvariance betweentwo locationsonadversity quotientgroup. Butonthe secondhypothesis, there has been no significant interaction between location of residence and adversity quotient to adaptation on settlements, as evidenced receipt of H0, this hypothesis can not be verified based on the results of processing the data collected under the various possibilities that occur in decision hypothesis formulation, processresearch,andotherfactors. Keywords: adaptationsettlement, location of residence, adversity quotient